filosofijateolohii͏̈ jak haluzʹ filosofii͏̈ relihii͏̈: vyznačennja statusu dyscyplin = Philosophy of Theology as a Field of Philosophy of Religion: Determination of the Discipline Status - Khrystokin, Hennadii (Bogoslovskie razmyšlenija, 2018)
In the article the author came to the conclusion that theology requires a special philosophical study, which the philosophy of theology is able to implement. At the same time, depending on the consensus accepted by the scientific community, the philosophy of theology can optimally be part of the philosophy of religion as an independent branch of philosophical knowledge; It can also be a subdivision of the philosophy of religion as a branch of academic religious studies; can perform special reflexive tasks in the structure of philosophical theology. The subject of the philosophy of theology is the diversity of religious manifestations of religious, religious-philosophical and theological knowledge; the available religious theology concepts of theology; philosophical reflections on theology. In all cases, the philosophy of theology must be a critical, reflexive knowledge of theology, a set of philosophical methods and approaches for the comprehensive study of theology as religious knowledge, confessional discourse, cultural phenomenon, academic discipline.